The use of hospital-based nurses for the surveillance of potential disease outbreaks - Durrheim David N.; Harris Bernice N.; Speare Rick; Billinghurst Kelvin (The World Health Organization, 2001)
OBJECTIVE: To study a novel surveillance system introduced in Mpumalanga Province, a rural area in the north-east of South Africa, in an attempt to address deficiences in the system of notification for infectious conditions that have the potential for causing outbreaks. METHODS: Hospital-based infection control nurses in all of Mpumalanga?s 32 public and private hospitals were trained to recognize, report, and respond to nine clinical syndromes that require immediate action. Sustainability of the system was assured through a schedule of regular training and networking, and by providing feedback to the nurses. The system was evaluated by formal review of hospital records, evidence of the effective containment of a cholera outbreak, and assessment of the speed and appropriateness of responses to other syndromes. FINDINGS: Rapid detection, reporting and response to six imported cholera cases resulted in effective containment, with only 19 proven secondary cholera cases, during the two-year review period. No secondary cases followed detection and prompt response to 14 patients with meningococcal disease. By the end of the first year of implementation, all facilities were providing weekly zero-reports on the nine syndromes before the designated time. Formal hospital record review for cases of acute flaccid paralysis endorsed the value of the system. CONCLUSION: The primary goal of an outbreak surveillance system is to ensure timely recognition of syndromes requiring an immediate response. Infection control nurses in Mpumalanga hospitals have excelled in timely weekly zero-reporting, participation at monthly training and feedback sessions, detection of priority clinical syndromes, and prompt appropriate response. This review provides support for the role of hospital-based nurses as valuable sentinel surveillance agents providing timely data for action.